Religion and Politics in William Steel Dickson DD (1744-1824): Ulster-Scot Irishman and his Modernizing Thought-World - Hazlett, Ian (Scottish church history, 2019)
This essay presents the lineaments and origins of the core thinking of Steel Dickson, a typically controversial representative of the progressive eighteenth-century intelligentsia in the north of Ireland who were Presbyterian ministers and inclined to radicalising reform of politics and religion as well as, more tentatively, to the reformatting of fundamental theology. There will be reference to short studies and general interpretations of Dickson and, more particularly, some analysis of his publications including religio-political addresses and church sermons. Discussed will be the context of his association with the Society of United Irishmen and its evolving revolutionary path, as well as his links to other reform thinkers, politicians and churchmen in Ulster. The study argues that Steel Dickson's varied political involvement flowed consciously from his ethical and religious convictions. Further, that he embodied (with qualification) the impact of the Scottish Enlightenment and ‘Moderate’ Presbyterianism in Ireland – but along with strong appeal to biblical testimony and norms. Finally, it demonstrates with illustrations that the decisive shaping and reconstructing of the contours of Dickson's mind occurred during his studies at Glasgow University in its intellectual heyday.